Legal Study of Consumer Protection in Using Blockchain Based on Government Law - Hapsari, Recca Ayu; Sinurat, Dilmanta Sony Parsaoran (International Journal Labs, 2021)
Background: The concept of financial technology, adapted to technological advances and combined with the financial sector, is expected to introduce a more practical, secure and modern financial transaction process. Products that can be categorized into the field of fintech include payment processing (payments), investment, financial planning, financial research, transfers, buying and selling shares, and financing (lending) etc. Aim: This study aims to analyze the legal protection of digitalized crowdfunding agencies. Method: This study uses a normative and empirical legal approach. There are two types of data used: secondary data and primary data. Data collection through library and field surveys. The data analysis used is juridical qualitative. Findings: With regard to consumer protection, violations of criminal acts committed in the implementation of SCF may be subject to criminal sanctions. In this case, the Criminal Sanction is not regulated in the POJK SCF. However, criminal sanctions are regulated in the Capital Market Law concerning Capital Market Crimes. Sanctions for violations of Capital Market Crimes are regulated in Articles 103 to 110 of the Capital Market Law and are also regulated in POJK No. 3/POJK.04/2021. Sanctions for criminal acts in capital market activities include fines, confinement to imprisonment.